Positive chirality measures from chiroptical pseudoscalars: applications to carbon-containing molecular systems - Luzanov, A.V. (Functional Materials, 2015)
A new chirality quantification scheme is proposed based on a special procedure transforming molecular pseudoscalar into positive index. The optical rotatory strengths (estimated semiempirically) are used for the corresponding characterization of chiral molecules. We show several specific examples of using the present method. The focus is made on dissymmetric π-conjugated systems constituting some special molecular materials (helicens etc.). A simplified technique of partitioning the chirality index into atomic contributions is reported. For most presented examples, the atomic distribution of chirality are found to be highly delocalized over the whole carbon backbone.